Amplifying angels: Evidence from the INVEST program - Berger, Marius; Gottschalk, Sandra (Journal of Business Venturing, 2025)
This paper shows that angel investor grants encourage new investors to enter the risk finance market, where they syndicate investments with other investors. We argue that this results from the high cost of information acquisition for new investors. New investors bring additional capital into the market but provide little managerial support. However, as these investors join syndicates, ventures can raise larger financing amounts without compromising managerial support. Taken together, these factors positively affect the performance of entrepreneurial ventures. To test our hypotheses, we consider the case of Germany, where the federal government has introduced an investment grant for angel investors. Combining applicant data from the subsidy program with company and ownership information on the quasi-universe of German companies and a large-scale company-level panel survey covering over 900 angel-financed ventures to empirically assess our hypotheses provides strong support for our predictions. • Investigates angel investor subsidy program INVEST in Germany, focusing on the role of new investors • Links applicant records to ownership information on the quasi-universe of German companies and a company-level panel survey • Most new investors syndicate investments • Investor grant has positive growth effect and input additionality through better access to financial and managerial support